Effect of a C1-C2 Mulligan sustained natural apophyseal glide (SNAG) in the treatment of cervicogenic headache - Kocjan, Janusz (Journal of Education, Health and Sport, 2015)
Kocjan Janusz .Effect of a C1-C2 Mulligan sustained natural apophyseal glide (SNAG) in the treatment of cervicogenic headache. Journal of Education, Health and Sport. 2015;5(6):79-86. ISSN 2391-8306. DOI 10.5281/zenodo.18328 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A79-86 https://pbn.nauka.gov.pl/works/563527 http://dx.doi.org/10.5281/zenodo.18328 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.04.2015. Revised 28.05.2015. Accepted: 04.06.2015. EFFECT OF A C1-C2 MULLIGAN SUSTAINED NATURAL APOPHYSEAL GLIDE (SNAG) IN THE TREATMENT OF CERVICOGENIC HEADACHE Janusz Kocjan Medical University of Silesia, Faculty of Medicine, Katowice, Poland Summary Introduction: Cervicogenic headache (CGH) is a syndrome characterized by chronic hemicranial pain that is referred to the head from either bony structures or soft tissues of the neck. Purpose: The purpose of this study was to determine the efficacy of the C1-C2 cervival rotation SNAG mobilisation in treatment of cervicogenic headache. Material and methods: A total of 22 participants with CGH diagnosis were examined. To assess the disability associated with headache, The Headache Impact Test (HIT-6) and Headache Activities of Daily Living Index (HADLI) were used. Results: Mean values in both questionnaires presented as follows (before vs after, P-value): HADLI: 25,0 ±7,97 vs 2,4 ± 0,6, p<0,001; HIT-6: 68,2 ±7,9 vs 44,1 ± 5,6, p<0,001. Average values in FRT test was: 28°(SD=7°) vs 40° SD=5°), p<0,001. Significant reduction of headache symptoms and improvement of range of movement in upper cervical region after use of Mulligan treatment were noted. Conclusions: Present study demonstrated efficacy of Mulligan manual therapy in CGH treatment. However, further research is needed. Key words: cervicogenic headache, Mulligan, SNAG.